1986
DOI: 10.1111/j.1398-9995.1986.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐Specific IgE Antibodies against Antigenic Components in Cow Milk and Milk Substitutes

Abstract: Crossed radioimmunoelectrophoresis (CRIE) was used to study the presence of serum IgE against antigenic components of cow milk in 21 selected milk-allergic patients. The amount of each IgE specificity was estimated by a scoring system. The milk-allergic children had mainly IgE against alpha-lactalbumin, beta-lactoglobulin, albumin and immunoglobulin, the four major proteins of bovine whey, as well as IgE against three casein components. A serum pool from 1000 normal adults had IgE against the same whey protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
7

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 10 publications
3
65
1
7
Order By: Relevance
“…This observation was supported by studies with RAST, skin test, histamine release, and blast transformation of lymphocytes, among other methods (4,(6)(7)(8)(9)(10).…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…This observation was supported by studies with RAST, skin test, histamine release, and blast transformation of lymphocytes, among other methods (4,(6)(7)(8)(9)(10).…”
mentioning
confidence: 50%
“…However, further studies on the allergenic behavior of hypoallergenic substitutes for cow's milk showed that casein was an important allergen (4,6). This observation was supported by studies with RAST, skin test, histamine release, and blast transformation of lymphocytes, among other methods (4,(6)(7)(8)(9)(10).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Wal, 1998 and The main characteristic that should be underlined is the multiplicity and diversity of proteins that are involved in cows' milk allergy. Sensitivities to the various cows' milk proteins have been demonstrated by Goldman et al (1963 a and b), Gjesing et al (1986) and Docena et al (1996). Polysensitisation to several proteins occurs often and all milk proteins appear to be potential allergens.…”
Section: Structure Function and Allergenic Properties Of Main Milk Pmentioning
confidence: 96%
“…Iz razloga sto P-laktoglobиJjn njje prisutan u humanom mleku, ovaj protejn је dugo vremena smatran najvainijjm alergenom kravljeg mleka (307)(308)(309) Hidvegi i saradnici (2002.) (324) su ispitivali nivo serumskih imunoglobиlina na razlicite proteine kravljeg mleka и pedesetoro dece sa alergijom na kravlje mleko, da…”
Section: Proteioi Hrane U Etiologiji Obolenj Aunclassified